ANALISIS TINGKAT KEPUASAN PASIEN BPJS DI POLI PENYAKIT DALAM RSUD LEWOLEBA DI NUSA TENGGARA TIMUR - Beda, Bernardus Yoseph; Madiistriyatno, Harries; Panjaitan, Eddy H.H. (ITB AAS Indonesia Surakarta, 2024)
The objectives of this research are: 1) To determine and analyze the influence of Reliability on Patient Satisfaction 2) To determine and analyze the influence of Guarantee on Patient Satisfaction 3) To determine and analyze the influence of Physical Evidence on Patient Satisfaction 4) To determine and analyze the influence of Empathy on Satisfaction Patients 5) To find out and analyze the influence of Responsiveness on Patient Satisfaction 6) To find out and analyze the influence of Reliability, Guarantee, Physical Evidence, Empathy and Responsiveness on BPJS Patient Satisfaction at the Internal Medicine Clinic of Lewoleba Regional Hospital. This research has a quantitative approach, descriptive and associative type. In this study, the author narrowed the population to 112 BPJS patients at the Internal Medicine Clinic, Lewoleba Regional Hospital. The sampling technique used in this research was the Slovin formula, and the data analysis technique used was the linier regression anÃ¡lisis. Based on the analysis carried out, it can be concluded that reliability, guarantee, physical evidence, physical evidence and empathy can significantly, either individually or collectively, influence BPJS patient satisfaction at the Internal Medicine Clinic at Lewoleba Regional Hospital. Keywords: Reliability, Guarantee, Physical Evidence, Empathy, Responsiveness, Patient Satisfaction